The Mediating Role of Social Capital in Islamic Work Ethic, Organizational Commitment, and Lecturer’s Performance - Pardiman, Pardiman; Sudiro, Achmad; Troena, Eka Afnan; Rofiq, Ainur (International Review of Management and Marketing, 2017)
The success of higher educations in producing intelligent, noble, skillful, and selfdeveloping graduates with good personality to improve the nation‘s competitiveness in globalization era is very much determined by lecturer‘s performance. However, various problems in the performance hamper the advancement of higher educations, especially private Islamic ones. The poor implementation of Tridharma Perguruan Tinggi (tree role of higher education), particularly in research, public service, and writing scientific paper’s, not to mention moonlighting behavior, must be enhanced through accurate problem identification and countermeasure. This study tries to measure the influence of Islamic work ethic and organizational commitment on lecturer performance, identify the mediating role of social capital on the influence of work satisfaction, and determine the moderating effect of Islamic work ethic on the relation between lecturer‘s performance on their satisfaction. This study uses data from 236 lecturers, selected through random sampling technique, of grade-A private Islamic higher educations. Using WarpPLS 5.0, the results of the analysis show that Islamic work ethic and organizational commitment plays a significant role in improving lecturer’s performance. Although, social capital is not significant to the performance, it partially mediates the influence of Islamic work ethic and organizational commitment to the performance. In addition, organizational commitment partially mediates the influence of Islamic work ethic on the performance. To improve this study, following researches on private Islamic higher educations of lower grades will be beneficial Keywords: Social Capital, Knowledge Sharing Behavior, Organizational Commitment, Lecturer Performance, Work Satisfaction, Islamic Work Ethic JEL Classifications: D8, L2 DOI: https://doi.org/10.32479/irmm.5740